Aspek Mutu Produk Roti Tawar untuk Diabetesi Berbahan Baku Tepung Porang dan Tepung Suweg - Dwi Agustiyah Rosida, Richardus Widodo Setijanen Djoko Harijanto (AGROKNOW, 2014)
Abstract. One of the more prominent food trend is increasingly exploration of food products that have a low glycemic index, especially for diabetics. Foods that have a low glycemic index is very good for diabetics.Plain bakery products from wheat flour known as food products are high glycemic index. Although there is a trend that more and more Indonesian people consume wheat bread from which raw materials, namely white flour, have to be imported, there are potential flour substitution ingredients native to Indonesia because it has a lower glycemic index than wheat flour. Two flour substitution materials developed as a potential food stock substitution of wheat flour is flour of porang plant (Amorphophallus muelleri Bl) and suweg (Amorphophallus campanulatus BI).The purpose of this study was to determine the optimal composition between wheat flour and flour or flour porang and suweg to be processed into bread low-IG . Benefit from an increase in value -added research is plant porang and suweg that still only sold as a powder, as well as obtaining the functional diversification with cheap raw materials from the local source. This study suggests that the substitution of flour and flour suweg porang till the 10% does not significantly degrade the quality of plain bread both in terms of physical, chemical and sensory.Kata kunci: Roti tawar, diabetesi, tepung porang, tepung suweg